The Influence of Brand Image on Visitor’s Decision and Satisfaction at Tourism Destination Lego-Lego Sulsel - Syawalia, Nurul; Jaya Gosari, Benny Audy; Adhawati, Sri Suro (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
The Impact of Brand Image on Visitors' Decisions and Satisfaction at Tourism Destination Lego-Lego Sulawesi Selatan. This study uses quantitative associative methods, namely research that aims to determine the effect or relationship between two or more variables. This research was conducted on January 25 – February 1 at Lego-Lego Sulsel in Makassar City. Sampling, using non-probability sampling method supported by accidental sampling technique. The data sources used are primary and secondary data and then analyzed using Validity, Reliability, and Simple Regression Tests. Based on the Simple Regression Test results, Brand Image (X) has a positive and significant effect on the decision to visit Lego-Lego Tourism Destinations in South Sulawesi. This can be seen from the significance of Brand Image (X) 0.000 < 0.05. And the value of the t table = 1.98552, meaning that the value of tcount = greater than ttable (7.038 > 1.98552) as well as the results of the Partial significance test (T-Test) to prove the impact of the Brand Image variable (X) on visitors' satisfaction (Y2) Brand Image variable (X) has a positive and significant effect on visitors' satisfaction at Lego-Lego South Sulawesi Tourism Destinations. This can be seen from the significance of Brand Image (X) 0.000 < 0.05. And the value of the tcount is 1.9552, meaning that the value of the tcount = greater than the ttable (12.032 > 1.98552).